Geophysical prospection in tin mineral occurrence associated to greisen in granite São Sepé (RS) - Silva,Marly Aparecida (2018)
Abstract The discovery of new mineral resources involves various research techniques through direct and indirect studies. The geophysical methods are important tools in the detection of deep deposits because they use the contrast between the physical properties of the hosting rocks and the mineralized zone. In this sense, electrical geophysical methods are widely used in the prospecting of sulfide deposits. This work presents and discusses the results of the application of the Induced Polarization geophysical method in the investigation of a tin mineral occurrence associated with greisen, located on the western border of São Sepé Granite. The study area is located in the central portion of the Rio Grande do Sul State, in the municipality of São Sepé (RS), housed in the metavolcano-sedimentary rocks of the Vacacaí Metamorphic Complex. Six lines of electrical tomography were parallel arranged in the N30W direction. The 2D inversion models allowed to identify areas of high chargeability (above 5.0 mV/V), possibly attributed to areas with sulfide accumulation. The areas with low values (below 1.9 mV/V) area associated with soil and rocks absent of mineralization. Through the 3D visualization models, it was possible to identify that the mineralized zone apparently has continuity for more than 36 m. These models also allowed identifying the morphology and the lateral continuity of the sulfide zone. Thus, the results of this work demonstrate the possibility of using Induced Polarization in the research of cassiterite deposits with associated sulfides due to the contrast of physical properties obtained from the high polarizability of the sulfides.